Língua, fala, sujeito em Saussure e Benveniste - Normand, Claudine (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2014)
I shall attempt to show in this paper that reading the CLG from a structural and sociological view point long has hidden the importance of speech (parole) in the «socio-historical phenomenon» of language operation. A «semiologic view point» in reading Saussure allows to stress this importance by re-introducing subject and time. Benveniste’s viewpoint, preoccupied as he was with his own theory of the « double signifiance » and of the two linguistics (semiotic/semantic), re-introduces the subject in a completely different way which leads him on the one hand to a more structuralist interpretation of Saussure, and, on the other hand announcing a theory of subjectivity and discourse, to turn towards a philosophical view of language.